50 years of hot plasma diagnostic with heavy ion beam probing (HIBP) at the Kharkov institute of physics and technology - Krupnik, L.I. (Вопросы атомной науки и техники, 2021)
An overview describes the evolution of HIBP diagnostics from the origins till today. The progress in the beam technology is presented by examples of HIBPs in tokamaks and stellarators. At the beginning, HIBP provided timeaveraged measurements of plasma potential in single space location, then it evolves to time-resolved measurements of radial distributions and finally it becomes a multi-purpose diagnostics to study the temporal evolution of 2D distributions of potential and turbulence, including the long-range potential correlations with dual HIBP. Highlights in plasma potential profile evolution, a link between potential, density and confinement, geodesic acoustic modes, steady and chirping Alfvén eigenmodes, turbulent particle flux are presented. Представлено огляд розвитку діагностики зондування плазми пучком важких іонів (ЗППВІ) від витоків до сьогодення. Прогрес у пучковій технології представлений на прикладах ЗППВІ в токамаках і стелараторах. Спочатку методом ЗППВІ вимірювала усереднені за часом потенціал плазми в одній точці, потім він дозволив знаходити радіальні розподіли з часовою роздільною здатністю, і, нарешті, він стає багатоцільовою діагностикою для вивчення часової еволюції двовимірних розподілів потенціалу і турбулентності, включаючи далекодіючі кореляції потенціалу, вимірювані здвоєним ЗППВІ. Детально розглянуто еволюцію профілю потенціалу плазми, зв'язку між потенціалом, густиною і утриманням, геодезичні акустичні моди, стаціонарні і чирпіровані альфвенівські власні моди, турбулентний потік частинок. Представлен обзор развития диагностики зондирования плазмы пучком тяжелых ионов (ЗППТИ) от истоков до сегодняшнего дня. Прогресс в пучковой технологии представлен на примерах ЗППТИ в токамаках и стеллараторах. Вначале методом ЗППТИ измерялся усредненный по времени потенциал плазмы в одной точке, затем он позволил находить радиальные распределения с временным разрешением, и, наконец, он становится многоцелевой диагностикой для изучения временной эволюции двумерных распределений потенциала и турбулентности, включая дальнодействующие корреляции потенциала, измеряемые сдвоенным ЗППТИ. Подробно рассмотрены эволюция профиля потенциала плазмы, связи между потенциалом, плотностью и удержанием, геодезические акустические моды, стационарные и чирпированные альфвеновские собственные моды, турбулентный поток частиц.